1978
DOI: 10.1139/f78-202
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of Serum Thyroxine and Triiodothyronine Levels in Yearling Coho Salmon, Oncorhynchus kisutch, by Dietary Mirex and PCBs

Abstract: Yearling coho salmon, Oncorhynchus kisutch, were fed diets contaminated with PCBs (500 μg or 50 μg/g dry feed), Mirex (50 μg or 5 μg/g dry feed), or a mixture of Mirex and PCBs (5 μg Mirex + 50 μg PCB/g dry feed) daily for 2 or 3 mo. Serum T3 and T4 levels were significantly reduced in fish fed the high Mirex diet for 2 or 3 mo. Serum T3 levels were reduced in fish fed the high PCB diet for 3 mo. Serum T3 and T4 levels were significantly reduced in fish fed the mixed Mirex–PCB diet for 3 mo. The significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…Changes in thyroid histological appearance and plasma thyroid hormone levels were reported in coho salmon (Oncorhynchus kisutch) and chinook salmon (Oncorhynchus tshawytscha) collected in Great Lakes (Leatherland, 1993). Salmonids were fed by Aroclor mixtures to determine if PCBs caused these changes, but no conclusive results could be obtained (Leatherland and Sonstegard, 1978;Leatherland and Sonstegard, 1980). Given the equivocal impact of experimental exposure of PCB mixtures on trout and salmon thyroid measures, it was concluded that other factors than PCBs may cause thyroid disruption of the Great Lakes salmon (Leatherland, 1993).…”
Section: Relationship Between Thyroid Parameters and Pcb Contaminationmentioning
confidence: 99%
“…Changes in thyroid histological appearance and plasma thyroid hormone levels were reported in coho salmon (Oncorhynchus kisutch) and chinook salmon (Oncorhynchus tshawytscha) collected in Great Lakes (Leatherland, 1993). Salmonids were fed by Aroclor mixtures to determine if PCBs caused these changes, but no conclusive results could be obtained (Leatherland and Sonstegard, 1978;Leatherland and Sonstegard, 1980). Given the equivocal impact of experimental exposure of PCB mixtures on trout and salmon thyroid measures, it was concluded that other factors than PCBs may cause thyroid disruption of the Great Lakes salmon (Leatherland, 1993).…”
Section: Relationship Between Thyroid Parameters and Pcb Contaminationmentioning
confidence: 99%
“…In laboratory studies in which both rainbow trout and coho salmon were fed mirex and polychlorinated biphenyls (PCBs), serum levels of both thyroxine (T,) and triiodothyronine (T,) were significantly reduced in fish fed 500 pg mirex per gram food; however, no significant changes were observed in fish fed 500 pg Aroclor 1254 per gram food [139,146]. No changes in thyroid histology were observed, suggesting the changes in thyroid hormones were due to altered peripheral metabolism of the hormones.…”
Section: Dirnethanonaphthalene)mentioning
confidence: 99%
“…The serum T3 levels in DBA/2 mice were elevated following consumption of coho salmon from the Pacific Ocean. Hypothyroidism has been reported in rats following dietary consumption of Lake Ontario coho salmon (23,24) and in coho salmon following dietary exposure to mirex and PCBs (25). The health problems associated with hypothyroidism in adult humans may be correctable with dietary supplements; however, the level ofrisk to the developing fetus is potentially very serious and may affect embryonic physical and mental development.…”
Section: Discussionmentioning
confidence: 99%